األدوار الجديدة لمحمؼ األطمسي من منظور السياسة الخارجية األمريكية - مسعودي عبد الحميم (المسيلة, 2023)
كانت نشأة حمؼ شماؿ األطمسي استجابة لجممة مف االستحقاقات عسكرية، سياسية، أمنية وقومية ودولية، والدولية والتي كاف ظيورىا في مرحمة ما بعد الحرب العالمية الثانية، والتي تمخصت في تحقيؽ أمف أوربا، ومع بروز صراعات و حروب أخرى خارج القارة األوربية، وتطويؽ االتحاد السوفياتي وشرؽ أوربا الشيوعي ومنع التأثيرات العسكرية وااليدلوجية الشيوعية في االنتقاؿ الى غرب أوربا، وكذا ردع السوفيتي عف التفكير في اليجوـ عمى أوربا الغربية، وتشكيؿ حاجز عسكري وأمني في مواجية المد الشيوعي. وكاف ليذا الحمؼ تأثير عمى كامؿ دوؿ العالـ بصفة عامة وعمى المنطقة العربية بصفة خاصة، وظير جميا في منطقة الشرؽ األوسط ومنطقة الخميج العربي بعد أحداث 11 سبتمبر وكانت لو آثار عمى المنطقة مزاؿ مفعوليا إلى يومنا ىذا. الكممات المفتاحية: حمؼ شماؿ األطمسي، الشرؽ األوسط، الخميج العربي، االستراتيجية األمريكية. Abstract: NATO's emergence was in response to a variety of military entitlements political, national and international security, and its emergence in the post-World War II era, which is summarized in the achievement of European security, and with the emergence of conflicts and other wars outside the European continent, The Soviet Union and the Communist East of Europe cordoned off and prevented communist military and ideological influences in moving to western Europe as well as deterring the Soviet from thinking about attacking Western Europe and forming a military and security barrier in the face of the communist tide. This Alliance has had an impact on the entire world in general and on the Arab region in particular. It has been visible in the Middle East and the Arabian Gulf region after the events of 11 September and has had effects on the region. Keywords: NATO, Middle East, Persian Gulf, American strategy.
Keywords: حلف الشمال الاطلسي - الشرق الاوسط - الخليج العربي الاستراتيجية الامريكية